The Payne Index of Ministry Styles: a lens on clergy activity from the perspective of psychological type theory. Issue 4 (21st April 2021) - Payne, V. John; Lewis, Christopher Alan
ABSTRACT: The present study examines the data collected from two clergy surveys conducted within the Church in Wales a decade apart (mid-1990s and mid-2000s). In both surveys the Payne Index of Ministry Styles was found to be reliable. Although the data appear to be consistent over the 10 years, there are exceptions to this, suggesting two changes in the ways in which clergy serving in the Church in Wales were conceptualising their ministry. The first change was reflected in both greater priority being ascribed to ministry characteristics associated with introversion and lower priority being ascribed to ministry characteristics associated with extraversion. The second change was reflected in both greater priority being ascribed to ministry characteristics associated with intuition and lower priority being ascribed to ministry characteristics associated with sensing. The question raised by these findings is this: Do the differences found in the two surveys reflect the changing role of clergy in a declining Church?